2015
DOI: 10.4172/2329-8863.1000174
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Use Practices and Perceptions of Vegetable Farmers in the Cocoa Belts of the Ashanti and Western Regions of Ghana

Abstract: Chemical pesticides are commonly used in the management of pests and diseases in vegetable production in Ghana. However, there is increasing concern about the adverse effects this use has on public health and the environment. A study was conducted to assess how much farmers' know about the safe handling and use of pesticides, and what they perceive to be the hazards around their use. In-depth field surveys was undertaken with 437 sampled vegetable producers and complimented with focus group discussions and fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 17 publications
6
23
0
Order By: Relevance
“…However, in some farms these pesticide containers were found close to water bodies. Similar observations were made by Ntow et al (2006) and Afari-Sefa et al (2015). According to Ntow et al (2006), where farms are close to drinking water sources and waterways (which is the case in many farming communities in this study area) the disposal of unwanted pesticide solutions and empty containers on the field presents a pollution problem for those who drink from these water sources as well as aquatic systems which are sources of livelihood for some communities.…”
Section: Washing Of Personal Protective Equipment (Ppe) After Pesticisupporting
confidence: 83%
See 2 more Smart Citations
“…However, in some farms these pesticide containers were found close to water bodies. Similar observations were made by Ntow et al (2006) and Afari-Sefa et al (2015). According to Ntow et al (2006), where farms are close to drinking water sources and waterways (which is the case in many farming communities in this study area) the disposal of unwanted pesticide solutions and empty containers on the field presents a pollution problem for those who drink from these water sources as well as aquatic systems which are sources of livelihood for some communities.…”
Section: Washing Of Personal Protective Equipment (Ppe) After Pesticisupporting
confidence: 83%
“…This may be an important source of pesticides exposure (Lekei et al 2014). Similar observations were made by Tijani (2006), Ntow et al (2006), AntwiAgyakwa (2013), Lekei et al 2014 andAfari-Sefa et al (2015). Empty pesticides containers were observed on cocoa farms during the field survey which confirmed what the farmers said.…”
Section: Washing Of Personal Protective Equipment (Ppe) After Pesticisupporting
confidence: 76%
See 1 more Smart Citation
“…They tend to re-use the same pesticide and increase its concentration when it is no longer effective. They also usually ignored the spray direction of pesticides and disposed the containers irresponsibly, which may increase the risk of water and soil contaminations (Ntow et al, 2006;Afari-Sefa et al, 2015). And lead to cross exposure to public health pests such as Aedes, making them resistant to these insecticides.…”
Section: Discussionmentioning
confidence: 99%
“…This conforms to the observation that the majority of the respondents in the region are smallholder farmers, and is consistent with the report of MoFA, (2011) which states that agriculture in Ghana is predominantly on a smallholder basis. Afari-Sefa et al (2015) also reported that the majority of vegetable farmers in the Western and Ashanti regions of Ghana have small farm holdings, ranging from less than 0.4 ha up to 4 ha. (2015) where the majority of the vegetable farmers in the Ashanti, Brong Ahafo, Volta and Central regions of Ghana practiced mixed cropping.…”
Section: Demographic Characteristics Of Farmersmentioning
confidence: 99%